Market Opportunities and Challenges for Organic Products in Karnali Province, Nepal - Ammar Bahadur Rokaya,; Akhilesh Chandra Pandey, (Journal of Nepalese Management and Research, 2024)
This study investigates the perspectives and experiences regarding market opportunities and challenges of organic products in Karnali Province, Nepal. By conducting in-depth interviews with 30 participants, including farmers, entrepreneurs, and experts in the organic sector, the study aims to provide a comprehensive understanding of the organic market dynamics in this region. The findings reveal significant market opportunities driven by growing local and international demand for organic products, increased health consciousness, and environmental awareness. Integrated agro-tourism, government and NGO support, export potential, and local community empowerment further enhance the market prospects. However, several challenges impede the growth of the organic sector in Karnali Province, Nepal. These include limited infrastructure difficulties in obtaining organic certification, restricted market access, intense competition from conventional products, and a need for more technical skills and knowledge among farmers. Additionally, local consumer awareness and perception of organic products need improvement to sustain market demand. The study underscores the need for collaborative efforts from public and private stakeholders to invest in infrastructure, provide technical training, streamline certification processes, and enhance market access. Addressing these challenges can help maximize the potential of organic farming in Karnali Province, promoting sustainable economic growth, environmental conservation, and improved livelihoods for local communities.